COVID-19 Knowledge and Perception among Budding Nurses: A Questionnaire-Based Survey - Patidar, Kuldeep; Sharma, Maneesh; Gautam3, Ashish; K. Sharma, Dinesh; Jain, Jayesh (International Journal of Nursing Research, 2023)
Background and Aim: In COVID-19 pandemic, a global emergency, there is a scarcity of resources including workforce in health-care system. Budding nurses as additional workforce are being utilized in COVID-19 units, where their knowledge and perception about COVID-19 plays a key role in patient care as well as for their safety. There is a paucity of regional data on knowledge and perception of budding nurses about COVID-19. The present study was conducted with an aim to assess the knowledge and perception of budding nurses about COVID-19. Materials and Methods: In this online survey, 380 budding nurses participated. A 26-item semi-structured (9) knowledge and (10) perception-based questionnaire was responded by participants. Descriptive and inferential statistics were used to analyze the findings. Results: A significant number of participants were passably aware of the basic element of COVID-19, that is, etiological factor, incubation period, clinical symptoms, transmission, prevention, and treatments and majority (52.89%) budding nurses have shown positive perception toward COVID-19. Conclusion: The findings of this study revealed that knowledge and perception of budding nurses were significantly adequate and positive about COVID-19; however, in some areas, there was a substantial gap in knowledge; hence, periodic educational sessions regarding COVID-19 to budding nurses will help in curtailing the gap and they can be utilized as a better resource in a time of pandemic to overcome the shortage of manpower.